2006
DOI: 10.1269/jrr.47.1
|View full text |Cite
|
Sign up to set email alerts
|

Sucralfate Protects Intestinal Epithelial Cells from Radiation-Induced Apoptosis in Rats

Abstract: Radiotherapy for malignant pelvic disease is often followed by acute radiation colitis (ARC). It has been reported that sucralfate treatment has a protective effect against ARC, though the mechanisms of action are unknown. The effects of sucralfate on X-ray radiation-induced apoptosis was studied at 4 Gy in the colonic crypt cells of rats. Sucralfate enemas given prior to radiation resulted in the following: (1) reduction in number of apoptotic colonic crypt cells; (2) reduction in number of caspase-3 positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
2
20
0
3
Order By: Relevance
“…Recent research has also demonstrated that shortages of SCFAs greatly reduces the expression of the MUC-2 gene, which is the main agent responsible for transcription of the protein fraction of colon mucins 8,30 . SCF is a cytoprotective agent that has been used for more than three decades in the treatment of several disorders such gastritis, duodenal, stress ulcers, burns, skin lesions, and DII [14][15][16][17][18]32 . SCF does not have any adverse effects and it's use is known to have multiple beneficial effects on mucocutaneous wound healing, because the drug can induce the proliferation of dermal fibroblasts, and limiting the inflammation might decrease fibrosis formation and EGF expression as well as the expression of other factors involved in tissue repair processes 32,33 .…”
Section: Evaluation Of the Application Of Enemas Containing Sucralfatmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has also demonstrated that shortages of SCFAs greatly reduces the expression of the MUC-2 gene, which is the main agent responsible for transcription of the protein fraction of colon mucins 8,30 . SCF is a cytoprotective agent that has been used for more than three decades in the treatment of several disorders such gastritis, duodenal, stress ulcers, burns, skin lesions, and DII [14][15][16][17][18]32 . SCF does not have any adverse effects and it's use is known to have multiple beneficial effects on mucocutaneous wound healing, because the drug can induce the proliferation of dermal fibroblasts, and limiting the inflammation might decrease fibrosis formation and EGF expression as well as the expression of other factors involved in tissue repair processes 32,33 .…”
Section: Evaluation Of the Application Of Enemas Containing Sucralfatmentioning
confidence: 99%
“…Stimulating effects on vascular factors, such as angiogenesis, which play important roles in tissue repair, have been demonstrated by SCF 14,35 . The substance is a sucrose and sulfate-aluminum complex which, when in contact with gastrointestinal secretions, forms a viscous gel that adheres to the mucosa creating a physical barrier that protects the mucosa [15][16][17][18] . The complex formed, in addition to preventing the degradation of the mucus that covers the gastrointestinal epithelium has antimicrobial properties 31,36 .…”
Section: Evaluation Of the Application Of Enemas Containing Sucralfatmentioning
confidence: 99%
See 1 more Smart Citation
“…Sucralfate enemas prior to radiation lead to reduction in: (a) the number of apoptotic colonic crypt cells; (b) the number of caspase-3 positive cells; (c) oncogene p53 accumulation and p21 expression; and (d) proapoptotic Bax/anti-apoptotic Bcl-2 ratio in rats. Therefore, the protective effects of sucralfate against radiation colitis might be partially due to the suppression of radiationinduced apoptosis in the colon and the protection of the colonic epithelial stem cell region [61] . Sucralfate administration may be also effective in human radiation proctocolitis [62] .…”
Section: Chronic Radiation Colitis (Table 2)mentioning
confidence: 99%
“…23) Several studies have established that radiationinduced apoptosis is associated with the expression of p53-responsive protein in salivary gland 24) and hypoxic tumor cells. 25,26) In addition, it has been shown that synthetic and natural radioprotective agents such as amifostine, 27) sucralfate, 28) pentoxifylline, 29) and aloe polysaccharides 30) inhibit radiation-induced apoptosis by modulating the p53-dependent pathway. Detection of a change in the ratio of anti-to pro-apoptotic proteins such as Bcl-2 : Bax is important in confirming apoptosis.…”
Section: Discussionmentioning
confidence: 99%